Case Report: autosomal dominant distal motor neuropathy as a new phenotype of KIF21A-related disorders - Subbotin, Dmitrii; Tatarskiy, Eugene; Kuchina, Anna; Cherevatova, Tatiana; Krylova, Tatiana; Ryzhkova, Oksana; Skoblov, Mikhail; Murtazina, Aysylu (Frontiers in Genetics, 2025)
Heterozygous missense variants in the KIF21A gene are best known to cause congenital fibrosis of the extraocular muscles. A recent report by Borja et al., 2025 suggested that the KIF21A gene may also be associated with syndromic phenotype, including peripheral neuropathy, brain malformations, and strabismus. We report the second case of early-onset distal motor neuropathy associated with the KIF21A gene. The proband was a 6-year-old female patient who had normal brain MRI, while neurophysiological examination and lower limb muscle MRI both suggested peripheral neuropathy. Quad whole-genome sequencing of the proband, her healthy sibling, and parents identified a de novo missense variant, c.1991T>C, p. (Leu664Pro), in the KIF21A gene and two compound-heterozygous missense variants, c.274C>T, p. (Pro92Ser) and c.512A>G, p. (Asn171Ser), in the OXA1L gene. Since the clinical features were not fully consistent with the known phenotypes associated with KIF21A or OXA1L-related disorders, initial genetic analysis prioritized OXA1L. However, functional studies, including exploratory Western blot analysis and high-resolution respirometry failed to support the pathogenicity of the identified variants. Following the publication of a similar KIF21A-associated case, the c.1991T>C, p. (Leu664Pro) variant was re-evaluated and re-classified as likely pathogenic. Our case supports expansion of the KIF21A-related phenotype to include distal motor neuropathy without brain malformations, in addition to multiple reports of other KIF21-associated syndromic phenotypes. This finding suggests that the KIF21A gene should be considered in the differential diagnosis for patients presenting with childhood-onset distal motor neuropathies.